Costa Rica : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper analyzes economic developments in Costa Rica during the 1990s. The paper highlights that the government of Costa Rica initiated an economic program for 1991-92 aimed at lowering inflation, strengthening the balance of payments, and setting the stage for sustained economic growth. These objectives were to be achieved through restrained financial policies, an exchange rate policy aimed at maintaining export competitiveness, and liberalization of prices, international trade, and the exchange system. The reduction in the combined public sector deficit in 1991 was accompanied by a tightening of monetary policy.